Perkembangan Penerapan E Business Guna Mendorong Terwujudnya Green Banking Secara Berkelanjutan Pada Sektor Perbankan Indonesia - muhammad iqbal fasa; suharto; adib fachri; Bunga Nitami (Universitas Linggabuana PGRI Sukabumi, 2022)
This research discusses the development of digital business and matters related to environmental concepts that are now a concern and things that need to be considered in all fields. The method used in this research is descriptive qualitative by observing, reading, and reviewing related information and then concluding it. Based on the results of the study, it was found that the development of the application of digital business in the banking sector is directly proportional to the concept of green banking to be achieved.